Nurturing Teacher Resilience: Transformational Leadership as a Protective Factor Against Burnout - Marwani, Marwani; Megayanti, Windi; Ilias, Mohd Faeez (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the role of transformational leadership in overcoming teacher burnout in schools. This study uses a qualitative approach with a case study design, where data is collected through interviews, observations, and documentation. Techniques for filtering important information, presenting structured data, and drawing accurate conclusions based on existing findings are used to analyze the data. The results of the study indicate that transformational leadership in schools plays an important role in overcoming teacher burnout. Idealized influence creates a sense of trust and recognition while inspiring motivation and connects teachers' work to a larger purpose, thereby helping to reduce burnout. Intellectual stimulation encourages creativity and innovation through open communication, which also contributes to preventing burnout. In addition, individual consideration provides personalized support and supports the professional growth and emotional well-being of teachers, thereby reducing the risk of burnout in the school environment. This study provides implications for effective leadership practices in the educational context. It offers insights for principals and education managers to apply a transformational leadership approach to overcome teacher burnout in schools.